Digital dementia and its impact on human cognitive and emotional functioning - Bartosz Horoszkiewicz (Kazimierz Wielki University, 2022)
Digital dementia is a term coined by Spitzer and associated with a decline in mental abilities in memory, attention, and thinking by people who overuse new technologies. The aim of the study was to analyse the scientific literature in the field of new technology on digital dementia and its impact on human cognitive and emotional functioning. The study was based on a content analysis of current articles on Google Scholar on the topic of digital dementia. The negative phenomena associated with digital dementia and their impact on human cognitive and emotional functioning were presented. It is shown that inappropriate use of social media can be a risk factor and a source of mental health problems. A more important contemporary problem is not escaping from modern technology, but rather the rational ability to use it.